Vliv klíštěcích slin na fagocytózu borelií dendritickými buňkami - Maršálková, Eliška (Jihočeská univerzita, 2017)
In this study we examined the effect of the tick saliva from I. ricinus and the effect of recombinant protein IRS-2 from the saliva of I. ricinus on dendritic cells derived from the mice bone marrow. We studied their effect on the production of cytokines by dendritic cells after the stimulation by B. burgdorferi, their effect on the expression of genes, that participate in phagocytosis, and the impact of the tick saliva on phagocytosis of B. burgdorferi by dendritic cells.
The effect of the tick saliva on phagocytosis of borrelia by dendritic cells
Keywords: klíště; sliny; fagocytóza; dendritická buňka; IRS-2; borelie; Tick; saliva; borrelia; IRS-2; phagocytosis; dendritic cell